2020
DOI: 10.2147/mder.s275883
|View full text |Cite
|
Sign up to set email alerts
|

<p>Influence of Stent Flexibility on Artery Wall Stress and Wall Shear Stress in Bifurcation Lesions</p>

Abstract: Purpose Stent flexibility can influence clinical outcome, especially in bifurcation lesions. For instance, an overly rigid stent can impose mechanical stress on the artery at the stent edges and alter both arterial geometry and blood flow dynamics in bifurcations. This study investigated the influence of stent flexibility on vessel geometry, histology, wall stress, and blood flow dynamics in arterial bifurcations. Materials and Methods We compared arterial angulation, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Otherwise, the recanalized connection may lose its patency over time or worse, can promote stenosis in the once healthy vascular segment. [47][48][49][50][51] For instance, low velocity, oscillatory flow patterns have been shown to correlate with arterial stenosis and thus should be avoided via proper anastomotic geometry and angle of placement, all of which are better modelled prior to the procedure. Evaluating a variety of connection designs and angles in silico and via techniques, such as ultrasound or laser PIV, would allow us to avoid pathologic turbulent flows that will eventually result in restenosis of the reestablish vascular tree.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, the recanalized connection may lose its patency over time or worse, can promote stenosis in the once healthy vascular segment. [47][48][49][50][51] For instance, low velocity, oscillatory flow patterns have been shown to correlate with arterial stenosis and thus should be avoided via proper anastomotic geometry and angle of placement, all of which are better modelled prior to the procedure. Evaluating a variety of connection designs and angles in silico and via techniques, such as ultrasound or laser PIV, would allow us to avoid pathologic turbulent flows that will eventually result in restenosis of the reestablish vascular tree.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical observations have indicated that the rate of endothelialization is delayed when the stent is implanted at the artery bifurcation. This is due to the dramatic change in the direction of blood flow in the artery bifurcations, leading to a much higher shear stress on the vessel wall and insufficient endothelialization 21,22 . To further address the role of fibrin deposition in artery bifurcation endothelialization, we implanted a corroded iron stent in the iliac artery bifurcation (Figure 4a,b).…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the dramatic change in the direction of blood flow in the artery bifurcations, leading to a much higher shear stress on the vessel wall and insufficient endothelialization. 21 , 22 To further address the role of fibrin deposition in artery bifurcation endothelialization, we implanted a corroded iron stent in the iliac artery bifurcation (Figure 4a,b ). The fibrin‐coated iron stent and the S316L stent were used as controls.…”
Section: Resultsmentioning
confidence: 99%
“…Their results showed that the Palmaz-Schatz-shaped stent had the greatest maximum plastic strain and the largest diameter change but the highest maximum von Mises stress on plaque and arterial intima and media (Wei et al, 2019). Saito et al's investigation revealed that stent flexibility influences not only mechanical stress on the artery but also wall shear stress (WSS), which may induce local neointimal hyperplasia (Saito et al, 2020). Perrin et al's report revealed that increasing vessel curvature leads to stent graft kinks and inadequate apposition against the arterial wall (Perrin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%